The impact of multidimensional poverty on antenatal care service utilisation in Malawi - Amanda Grace Chatata; Gowokani Chijere Chirwa (Health Economics Review)
Abstract Background Poverty remains a key barrier to accessing essential maternal health services, particularly in low- and middle-income countries like Malawi. Despite the recognised importance of antenatal care (ANC) in ensuring healthy pregnancies as well as improving maternal and child health outcomes, ANC services remain underutilised by many women living in poverty. This underutilisation is not solely driven by a lack of financial resources but also by a range of non-monetary factors that constitute multidimensional poverty, such as limited access to education, healthcare services, and infrastructure. While much of the existing literature focuses on monetary poverty, this study explores how multidimensional poverty impacts ANC utilisation. By examining how various deprivations intersect to limit access to ANC, this research contributes to understanding the broader issue of healthcare inequality. Aim We assess the impact of multidimensional poverty (non-monetary) on antenatal care use in Malawi. Method Multidimensional poverty was constructed using the Forster-Akire method of the Oxford Poverty and Human Initiative (OPHI). We use data from the 2015–16 Demographic Health Survey (DHS), which includes information on women aged 15–49 who gave birth within five years of the survey. To mitigate selection bias, we use Propensity Score Matching (PSM) techniques for our principal analysis. Results Our findings reveal that 52% of women adequately utilised ANC services. About 8,428 women were identified as multidimensionally poor, and 4,685 were classified as non-poor. The results of our PMS analysis show a significant negative relationship between ANC utilisation and multidimensional poverty (B = 0.52; P < 0.008), indicating that multidimensionally poor women are less likely to use ANC services. Similarly, the timing of ANC visits also showed a negative relationship with multidimensional poverty (B = 0.26; P < 0.04), highlighting that multidimensionally poor women are less likely to attend ANC visits within the recommended first trimester. Conclusion The findings suggest that there is a need for sustainable investments in poverty alleviation programs to address and reduce multidimensional poverty as well as raise awareness of sexual and reproductive health concerns among adolescents and women in Malawi to improve maternal health outcomes.